2018
DOI: 10.1098/rsos.180996
|View full text |Cite
|
Sign up to set email alerts
|

Lower limb joint angle variability and dimensionality are different in stairmill climbing and treadmill walking

Abstract: The present study tested if the quadratic relationship which exists between stepping frequency and gait dynamics in walking can be generalized to stairmill climbing. To accomplish this, we investigated the joint angle dynamics and variability during continuous stairmill climbing at stepping frequencies both above and below the preferred stepping frequency (PSF). Nine subjects performed stairmill climbing at 80, 90, 100, 110 and 120% PSF and treadmill walking at preferred walking speed during which sagittal hip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…First, we only calculated the LyE starting from 120 gait cycles. This has been deemed a sufficient data length with limited gains in precision if more strides could have been included (Bruijn et al, 2009;Raffalt, Vallabhajosula, Renz, Mukherjee, & Stergiou, 2018;F. Riva et al, 2014;.…”
Section: Discussionmentioning
confidence: 99%
“…First, we only calculated the LyE starting from 120 gait cycles. This has been deemed a sufficient data length with limited gains in precision if more strides could have been included (Bruijn et al, 2009;Raffalt, Vallabhajosula, Renz, Mukherjee, & Stergiou, 2018;F. Riva et al, 2014;.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, harnesses worn during walking were reported to negatively affect ankle neuromuscular control (i.e., decreased organization of variability patterns) compared to the knee and hip [ 23 ]. In healthy young adults, joint angle variability during continuous stair mill climbing were similar across lower limb joints [ 24 ]. With known calf muscle impairments, which impact ankle contributions to walking in patients with PAD, levels of variability could differ across joints.…”
Section: Introductionmentioning
confidence: 99%